Acquisition, processing, and single-cell analysis of normal human breast tissues from a biobank - Poornima Bhat-Nakshatri; Natascia Marino; Hongyu Gao; Yunlong Liu; Anna Maria Storniolo; Harikrishna Nakshatri (STAR Protocols, 2022)
Summary: The Komen Tissue Bank is the only biorepository in the world for normal breast tissues from women. Below we report the acquisition and processing of breast tissue from volunteer donors and describe an experimental and analysis pipeline to generate a single-cell atlas. This atlas is based on single-cell RNA-seq and is useful to derive breast epithelial cell subcluster-specific gene expression signatures, which can be applied to breast cancer gene expression data to identify putative cell-of-origin.For complete details on the use and execution of this protocol, please refer to Bhat-Nakshatri et al. (2021).